Method for hydrogen production by biomass and waste plastic mixed and segmented gasification catalysis

CN122898296APending Publication Date: 2026-10-13NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611083574.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,生物质自身氢碳比较低,在气化制氢过程中容易受到供氢能力不足、焦油含量较高及产氢效率受限等问题的影响

Benefits of technology

1.本发明以废塑料作为生物质气化过程中的供氢体,与生物质组分协同转化,有利于改善气体产物分布,提高氢气产率,并实现废塑料资源化利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898296A_ABST
    Figure CN122898296A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of hydrogen production from biomass, and particularly relates to a method for hydrogen production by catalytic gasification of mixed biomass and waste plastics in sections. The specific technical scheme is as follows: a method for hydrogen production by catalytic gasification of mixed biomass and waste plastics in sections, inert gas is introduced into a double-section tubular furnace to form an inert reaction atmosphere; after the double-section tubular furnace is heated, water vapor is introduced, then the biomass and waste plastics are mixed and loaded into a gasification section reaction zone of the double-section tubular furnace, a catalyst is loaded into a catalytic reforming section reaction zone of the same reactor, a gasification reaction is carried out at high temperature, after the reaction is completed, the gas flows to the catalytic reforming section for catalytic reaction with the inert gas, after the catalytic reaction is completed, the gas is recovered after being condensed and dried in sequence. The present application uses waste plastics as a hydrogen donor in the process of biomass gasification, which is synergistically converted with the biomass components, is conducive to improving the distribution of gas products, increasing the hydrogen production rate, and realizing the resource utilization of waste plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomass hydrogen production technology, specifically to a method for staged gasification catalytic hydrogen production by blending biomass and waste plastics. Background Technology

[0002] Hydrogen has advantages such as high calorific value, wide availability, and clean combustion products, and is considered an important secondary energy source in the future energy system. Compared with traditional hydrogen production methods that use fossil fuels such as coal and natural gas as raw materials, biomass hydrogen production has advantages such as renewability, carbon neutrality, and wide availability of resources, making it an important pathway to achieve efficient utilization of biomass resources and clean energy production.

[0003] Biomass is mainly composed of three components: cellulose, hemicellulose, and lignin. The chemical structures, pyrolysis and gasification behaviors, and gas production characteristics of these components differ significantly, which greatly influences the gas composition, hydrogen yield, tar formation, and carbon conversion rate during the gasification hydrogen production process. However, biomass itself has a low hydrogen-to-carbon ratio, making it susceptible to problems such as insufficient hydrogen supply capacity, high tar content, and limited hydrogen production efficiency during gasification hydrogen production. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for staged gasification catalytic hydrogen production from biomass and waste plastics.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention discloses a method for staged gasification catalytic hydrogen production from biomass and waste plastics. An inert gas is introduced into a two-stage tubular furnace to create an inert reaction atmosphere. After heating the two-stage tubular furnace, steam is introduced. Then, a mixture of biomass and waste plastics is loaded into the gasification reaction zone of the two-stage tubular furnace. A catalyst is loaded into the catalytic reforming reaction zone of the same reactor. The gasification reaction is carried out at high temperature. After the reaction is completed, the gas flows with the inert gas to the catalytic reforming zone for catalytic reaction. After the catalytic reaction is completed, the gas is successively condensed, dried, and recovered.

[0006] Preferably, the biomass is any one of microcrystalline cellulose, xylan, and alkali lignin.

[0007] Preferably, the catalyst is Fe / CaO-Al2O3, and the ratio of the catalyst to the total mass of biomass and waste plastics is 1:1.

[0008] Preferably, the temperature of the gasification reaction is 600-900℃, and the temperature of the catalytic reaction is 800℃.

[0009] Preferably, the ratio of water vapor to the total mass of biomass and waste plastics is 0.5-2.0.

[0010] Preferably, the mass ratio of biomass to waste plastic is 1:1.

[0011] Preferably, the waste plastic is low-density polyethylene.

[0012] Preferably, the biomass and waste plastics are dried at 105°C for 10 hours, then crushed and passed through an 80-mesh sieve.

[0013] The present invention has the following beneficial effects: 1. This invention uses waste plastics as hydrogen donors in the biomass gasification process, which co-convert with biomass components, which is beneficial to improving the distribution of gaseous products, increasing hydrogen yield, and realizing the resource utilization of waste plastics.

[0014] 2. This invention takes the three major components of biomass—cellulose, hemicellulose, and lignin—and waste plastics as research objects. It conducts staged gasification catalytic hydrogen production experiments by blending the three biomass components with waste plastics, exploring the synergistic hydrogen production laws of different biomass component and waste plastic blending systems, and analyzing the influence mechanism of operating conditions and catalysts on hydrogen yield and gas product distribution. This provides a theoretical basis and experimental foundation for the synergistic and efficient hydrogen production of biomass and waste plastics. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the structure of the present invention; Figure 2 GC-MS images of the liquid products after separate vaporization of the three components; Figure 3 Figures showing the gas production characteristics of the three components after individual gasification: (a) relative content of gaseous products; (b) total gas production and H2 production. Figure 4 Figure 1 shows the gasification characteristics of the three components after blending with LDPE: (a) relative content of gaseous products; (b) total gas production and H2 production. Figure 5 The graph shows the relative content of products in the microcrystalline cellulose-LDPE blend system at different vaporization temperatures. Figure 6 The graph shows the gas production of the microcrystalline cellulose-LDPE blend system at different gasification temperatures. Figure 7 The graph shows the relative content of products in the microcrystalline cellulose-LDPE blend system under different steam conditions. Figure 8 The diagram shows the gas production of the microcrystalline cellulose-LDPE blend system under different vapor ratios. Figure 9 The graph shows the relative content of products in the xylan-LDPE blend system at different vaporization temperatures. Figure 10The graph shows the gas production of the xylan-LDPE blend system at different gasification temperatures. Figure 11 The graph shows the relative content of products in xylan-LDPE blending systems under different steam conditions. Figure 12 Gas production diagram of xylan-LDPE blend system under different steam ratios; Figure 13 The graph shows the relative content of products in the alkali lignin-LDPE blend system at different gasification temperatures. Figure 14 The graph shows the gas production of the alkali lignin-LDPE blend system at different gasification temperatures. Figure 15 The graph shows the relative content of products in the alkali lignin-LDPE blending system under different steam conditions. Figure 16 The diagram shows the gas production of the alkali lignin-LDPE blend system under different steam ratios. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Unless otherwise specified, the technical means used in the implementation examples are conventional means well known to those skilled in the art.

[0018] This invention discloses a method for staged gasification catalytic hydrogen production from biomass and waste plastics, comprising the following steps: (1) The biomass and waste plastics were dried at 105°C for 10 hours, then crushed and passed through an 80-mesh sieve.

[0019] (2) Nitrogen cylinders are used to provide carrier gas. After the flow rate is controlled by a flow meter, the gas is introduced into the tube furnace to continuously purge and replace the air in the system to form an inert reaction atmosphere. The nitrogen flow rate is 100 mL / min.

[0020] (3) Set the target gasification temperature of the two-stage tubular furnace to 600-900℃ and the reforming temperature to 800℃. After heating to the target value by an electric heating furnace, water is supplied to the steam generator by an injection pump. The generated steam enters the gasification section along with the carrier gas. The steam flow rate is 25-100 mg / min. The mass ratio of steam to raw material S / B is controlled to be 0.5-2.0.

[0021] (4) After mixing biomass and waste plastic (low-density polyethylene LDPE) at a mass ratio of 1:1, the mixture is quickly loaded into the gasification section reaction zone (i.e., gasifier) ​​of the two-stage tubular furnace. The catalyst is loaded into the catalytic reforming section reaction zone (i.e., reformer) of the same reactor, and the valve is immediately closed. The mixed reaction raw materials undergo pyrolysis and steam gasification reactions in the high-temperature steam atmosphere of the gasification section to generate crude product gas containing small molecule gases and tar volatiles. The crude product gas flows with the carrier gas to the catalytic reforming zone in the later section of the reactor. Under the action of high temperature and catalyst, tar cracking, water-gas shift and hydrocarbon steam reforming reactions occur to complete the gas phase upgrading and obtain reformed mixed gas.

[0022] (5) After the catalytic reaction is completed, the generated mixed gas is recovered after condensation and drying. The condensation removes the tar components and liquid water from the mixed gas; then the dehydrated gas is passed into a drying device (using color-changing silica gel, drying at room temperature is sufficient; if the color-changing silica gel remains blue, it indicates that the water has been completely absorbed and the gas is dry; if the silica gel turns pink, it indicates that the silica gel has been hydrated and the desiccant needs to be replaced) to remove residual water vapor, and finally obtain the hydrogen-rich gas product; the dried gas is connected to a gas sampling bag for collection, and used for subsequent detection and analysis of gas components, total gas production and hydrogen production.

[0023] The biomass is any one of microcrystalline cellulose, xylan, and alkali lignin. The catalyst is Fe / CaO-Al2O3, and the mass ratio of the catalyst to the total mass of biomass and waste plastics is 1:1. The mass ratio of water vapor to the total mass of biomass and waste plastics is 0.5-2.0.

[0024] The present invention will be further described below with reference to specific embodiments.

[0025] This invention focuses on the three major components of biomass: microcrystalline cellulose to represent cellulose, xylan to represent hemicellulose, alkali lignin to represent lignin, and low-density polyethylene (LDPE) as a hydrogen donor from waste plastics. First, separate gasification experiments were conducted on each of the three components to analyze the distribution of gaseous products, total gas production, and hydrogen yield under unmixed conditions. Based on this, microcrystalline cellulose, xylan, and alkali lignin were blended with LDPE at a mass ratio of 1:1 to further investigate the impact of the waste plastic hydrogen donor on the gasification performance of the three components.

[0026] To clarify the regulatory effect of reaction conditions on the hydrogen production process, gasification experiments were conducted on three-component LDPE blended systems with varying gasification temperatures and steam ratios (S / B). The analysis focused on the changes in the volume fractions of major gaseous products such as CO, H2, CO2, and CH4, as well as the variations in total gas production and H2 yield. These experiments preliminarily obtained data on the gasification characteristics of the three biomass components individually, in blended gasification with LDPE, and under different operating parameters, providing a foundation for subsequent optimization of the staged gasification catalytic hydrogen production process.

[0027] Example 1 1. Analysis of each raw material component This invention selects microcrystalline cellulose, xylan, and alkali lignin as representative components of the three major components of biomass (cellulose, hemicellulose, and lignin), respectively. All three reagents were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Low-density polyethylene (LDPE) was purchased from Jilin Provincial Scientific Instruments Company as a hydrogen donor from waste plastics. Before the experiment, the four raw materials were dried at 105℃ for 10 hours, then pulverized and sieved to obtain 80-mesh particles, which were then placed in a sealed desiccator for later use. Elemental and industrial analyses of the experimental raw materials are shown in Table 1. Elemental analysis of the raw materials was performed using a Thermo Scientific FLASH 2000 instrument, and industrial analysis was conducted according to GB / T 28731-2012.

[0028] Table 1 Elemental and industrial analysis of experimental raw materials

[0029] 2. The specific steps of the experiment are as follows: like Figure 1 As shown, the entire experiment was conducted under an inert atmosphere, using high-purity nitrogen as the carrier gas. This setup maintains positive pressure inside the tubular furnace, ensuring the safety of the experiment and personnel, and also facilitates the removal and collection of gaseous products during catalytic co-gasification. The specific experimental steps are as follows: (1) Purge the system with high-purity nitrogen at a flow rate of 100 mL / min for 30 minutes to completely remove the air from the device, and check the airtightness of the system at the same time.

[0030] (2) Set the target gasification temperature and reforming temperature (800℃) for the two-stage tubular furnace. After reaching the target temperature at a heating rate of 10℃ / min, start the peristaltic pump to inject deionized water into the steam generator. The steam flow rates are as follows: when S / B=0.5, the steam inlet velocity is 25 mg / min; when S / B=1.0, the steam inlet velocity is 50 mg / min; when S / B=1.5, the steam inlet velocity is 75 mg / min; and when S / B=2.0, the steam inlet velocity is 100 mg / min.

[0031] (3) In a nitrogen atmosphere, the generated steam is introduced into the tubular furnace. The pre-weighed catalyst and raw materials are quickly added to the reformer and gasifier respectively, and the valves are immediately closed; the catalyst and raw materials are of the same mass, and the raw materials are biomass and waste plastics mixed at a mass ratio of 1:1.

[0032] (4) Collect the purified gas using a gas bag. During the preparation stage, analyze the gas using a gas chromatograph every 2 minutes. After 40 minutes of reaction, the gaseous product is mainly nitrogen, and the concentration of the effective component has dropped to a very low level and tends to stabilize, indicating that the pyrolysis gasification experiment is complete. Therefore, the fixed duration of each reaction is set to 40 minutes. Subsequently, the gaseous products collected in the gas bag are analyzed by gas chromatography.

[0033] (5) Remove the conical flask and extract the liquid phase product (tar and aqueous organic matter) collected through the condensation system. Extract and separate the organic components with dichloromethane solution, and then evaporate the dichloromethane in a constant temperature water bath to obtain the organic components. The specific process is as follows: 1) Mix the liquid phase product containing the target organic components with dichloromethane thoroughly in a separatory funnel and shake. After shaking, let it stand until the dichloromethane settles in the lower layer. After the liquid has completely separated into layers, slowly release the dark-colored dichloromethane organic phase from the bottom of the separatory funnel and collect it in a clean container. 2) Add an appropriate amount of anhydrous sodium sulfate (Na2SO4) to the combined organic phase to absorb water, and then shake and let it stand for a period of time until the sodium sulfate powder no longer clumps and can flow freely, which indicates that the water has been basically removed. Filter the desiccant with filter paper, and the filtrate obtained is a pure dichloromethane solution containing the target organic components. 3) Place the container containing the extract in a water bath at a constant temperature of 50°C and heat to evaporate. Once the solvent has been mostly evaporated, the concentrated organic components are obtained. The entire operation is carried out in a fume hood to ensure safety.

[0034] (6) Turn off the peristaltic pump, remove the reacted raw material mixture and catalyst, and continue to purge the system with nitrogen for 30 minutes before proceeding to the next set of experiments.

[0035] Each experiment was repeated three times under the same conditions, and the average value of the tests was taken as the final experimental result.

[0036] The catalyst used was Fe / CaO-Al2O3, prepared as follows: The catalyst was prepared by co-impregnation method, using 10wt.% Fe / CaO-Al2O3 as an example. 1.446g Fe(NO3)3·9H2O, 0.942g CaO, and 0.858g γ-Al2O3 were weighed and impregnated together in deionized water. The resulting precursor solution was magnetically stirred in an 80℃ water bath for 6h, dried in an oven at 120℃ for 12h, then calcined in air in a muffle furnace at 850℃ for 5h, and finally ground and sieved to obtain 80-mesh catalyst particles.

[0037] Example 2: Separate gasification of three components and analysis of results The preparation method of Example 1 was followed without the use of a catalyst. The collected liquid and gaseous products were then analyzed.

[0038] Analysis results of liquid phase and gas phase products: 1. GC-MS analysis of liquid products after separate vaporization of the three components An Agilent 7890B gas chromatograph coupled with an Agilent 5977B mass spectrometer detector was used. The gas chromatograph was equipped with an HP-5MS capillary column, 30 m long, 0.25 mm inner diameter, and 0.25 μm film thickness. High-purity helium was used as the carrier gas, with a flow rate of 1.0 mL / min and a split ratio of 50:1. The initial temperature was 40℃, held for 3 min, then increased to 280℃ at a rate of 10℃ / min and held for 5 min. The injection port temperature was 280℃, and the injection volume was 1.0 μL. The liquid product was extracted with dichloromethane and then analyzed. The results are as follows: Figure 2 As shown.

[0039] from Figure 2 As can be seen, at a retention time of approximately 16 min, microcrystalline cellulose exhibits the highest response peak across the entire spectrum, with a signal intensity of 15%, indicating that the release of pyrolysis volatiles during gasification is relatively concentrated. Xylan, with a response intensity of 13% at the same retention time, is also a prominent signal peak across the entire spectrum. Both polysaccharide components show strong responses around 16 min, indicating that cellulose and hemicellulose undergo rapid decomposition in the early stages of gasification, generating relatively concentrated volatile organic compounds. From the overall peak shape, the response value of microcrystalline cellulose gradually decreases from 85% to 15% in the 0-16 min range, showing a continuous attenuation trend, indicating that its volatiles are mainly released in the early stages and the decomposition process is relatively rapid.

[0040] The signal distribution of xylan differs somewhat from that of microcrystalline cellulose. A secondary peak with a response value of 14% appears at 17 min, and the response value is 8% at 18 min. Several weak signals with a response value of 1% still exist in the 20-26 min range. This indicates that in addition to the easily cleaved polysaccharide backbone, the xylan structure also contains some side chain groups with slightly higher stability. The retention time of its cleavage products is delayed compared to the main peak, resulting in a more dispersed product distribution compared to microcrystalline cellulose.

[0041] The GC-MS signal distribution of alkali lignin differs significantly from the previous two. Its initial response is 135%, rapidly decreasing to 17% within the 0-8 min range. After 8 min, the response fluctuates between 1% and 13%, stabilizing at 1% after 35 min. Compared to the concentrated peak patterns of microcrystalline cellulose and xylan, alkali lignin exhibits a greater number of signal peaks and a wider distribution range, which is closely related to the complex functional groups such as aromatic rings, ether bonds, and methoxy groups in the lignin structure. The breaking of ether and carbon-carbon bonds between phenylpropane units in lignin generates various oxygen-containing aromatic compounds. These products exhibit significant differences in boiling points and polarities, resulting in a wider chromatographic retention time distribution.

[0042] In summary, there is a correlation between the structural stability of the components and the degree of complete gasification. The relatively concentrated pyrolysis products of microcrystalline cellulose and xylan indicate that the activation energy required for homolytic cleavage of glycosidic bonds in their molecular structures is more uniformly distributed, allowing the gasification process to be completed within a narrow temperature window. This is beneficial for the unified treatment of gaseous products in the subsequent catalytic reforming stage. In contrast, alkali lignin, due to the higher thermal stability of its aromatic ring structure, requires some pyrolysis products to be further converted into small-molecule gases at higher temperatures or longer residence times.

[0043] 2. Analysis of gas production characteristics of the three components through individual gasification Gas product analysis was performed using an Agilent 7890B gas chromatograph with online detection, equipped with a TCD and FID detector. The TCD was used for quantification of H2, CO, CO2, and CH4. The reaction conditions were as follows: vaporization temperature 700℃, vapor ratio S / B = 1.0, N2 carrier gas flow rate 100 mL / min, water vapor inlet flow rate 50 mg / min, and feed injection volume 2.0 g.

[0044] Depend on Figure 3 (a) It can be seen that microcrystalline cellulose gasification produces CO as the main gas, with the best hydrogen production level and the strongest overall gasification reactivity. Due to the removal effect of the acetyl side chain in the molecule, xylan has a significantly higher proportion of CO2 in the gasification products, and its hydrogen production is slightly lower than that of microcrystalline cellulose. Alkali lignin is limited by the stability of the aromatic macromolecular skeleton, and its hydrogen production is the lowest among the three, making it the most difficult to gasify and convert. Based on the results of the gas phase composition, the hydrogen production capacity of the three feedstocks is ranked as follows: microcrystalline cellulose > xylan > alkali lignin, which is consistent with the GC-MS analysis results, reflecting the regulatory role of the molecular structure of the feedstocks on the distribution of gasification products.

[0045] Depend on Figure 3 (b) It can be seen that the total gas production of microcrystalline cellulose is 1.50 Nm³. 3 / kg, hydrogen production is 0.303 Nm 3 / kg, the total gas production of xylan is 1.33 Nm 3 / kg, hydrogen production 0.243 Nm 3 / kg, the total gas production of alkali lignin is 1.08 Nm³. 3 / kg, hydrogen production 0.141 Nm 3 / kg. From microcrystalline cellulose to alkali lignin, the total gas production decreased by approximately 27%, while the hydrogen production decreased by 52%. The decrease in hydrogen production was significantly greater than the decrease in total gas production, indicating that alkali lignin not only had a lower overall gasification conversion rate during gasification, but also exhibited significantly lower hydrogen selectivity among the gaseous products compared to the other two components. This result corroborates the conclusion from GC-MS analysis that alkali lignin produced a wider variety of liquid products and a higher content of aromatic compounds. The aromatic ring structure in lignin has high thermal stability, and the hydrogen-containing intermediates generated from pyrolysis tend to stabilize in liquid-phase aromatic compounds or CH4 rather than being converted into H2. Microcrystalline cellulose, due to its regular molecular structure and concentrated distribution of glycosidic bond cleavage activation energies, exhibited the best total gas production and hydrogen production. Although xylan is also a polysaccharide component, it contains more branches and oxygen-containing side groups, requiring higher activation energies for further conversion of some pyrolysis products, thus its gas production performance falls between the two.

[0046] Example 3 Following the preparation method of Example 1, the gaseous and liquid products obtained, as well as their gas production characteristics under different operating parameters, were analyzed, as follows: 1. Analysis of Gas Production Characteristics of Three-Component Gas Blend with LDPE The H2 volume fraction of all three blended systems was significantly increased compared to the individual gasification processes. Figure 4 As shown in (a), the relative H2 content of the microcrystalline cellulose-LDPE blend system increased by approximately 40% compared to gasification alone; the relative H2 content of the xylan-LDPE blend system increased by approximately 48% compared to gasification alone; and the relative H2 content of the alkali lignin-LDPE blend system increased by approximately 63% compared to gasification alone. The alkali lignin-LDPE blend system showed the largest increase, indicating that LDPE has a more significant hydrogen supply compensation effect on low H2 / C ratio feedstocks. The relative CO2 content generally decreased, indicating that the addition of LDPE changed the oxygen distribution pathway in the system, and some oxygen was released as H2O rather than CO2 under hydrogen-rich conditions. The alkali lignin-LDPE blend system had the highest CH4 content, which is related to the fact that its methoxy side chain still dominates the CH4 formation pathway in the blend system. A horizontal comparison of the three blended systems showed that the H2 yield was ranked as follows: microcrystalline cellulose-LDPE > xylan-LDPE > alkali lignin-LDPE, consistent with the ranking of individual gasification. This indicates that the structural characteristics of the raw materials themselves are still the fundamental factor determining the hydrogen production performance, but the incorporation of LDPE significantly reduced the hydrogen production gap among the three components.

[0047] Will Figure 4 (b) Comparative analysis with the yields of individual gasification of the raw materials shows that the total gas production and hydrogen production of the three blended systems are significantly improved. LDPE promotes the forward water-gas shift reaction through a synergistic effect, effectively improving the overall gasification conversion degree and hydrogen production efficiency. In the three co-gasification systems, the difference in total gas production is relatively small, and the hydrogen production per unit of raw material shows a decreasing trend, in the order of microcrystalline cellulose-LDPE > xylan-LDPE > alkali lignin-LDPE. This difference stems from the stability of the biomass' molecular structure itself; alkali lignin has greater resistance to the cracking of its aromatic skeleton and the weakest synergistic hydrogen enhancement effect.

[0048] 2. Effect of gasification temperature on gas generation characteristics of microcrystalline cellulose-LDPE blend system Temperature gradient experiments were conducted on the co-gasification of microcrystalline cellulose and LDPE using a segmented fixed-bed gasification device. Four temperature variables were set: 600℃, 700℃, 800℃, and 900℃. The gaseous components were quantitatively detected using an Agilent 7890B gas chromatograph with a TCD detector. The volume fraction was determined using the external standard method. Microcrystalline cellulose and LDPE were blended at a mass ratio of 1:1, with a feedstock injection amount of 2.0 g and a vapor ratio S / B = 1.0. Figure 5 It can be seen that as the gasification temperature increases from 600℃ to 900℃, the volume fractions of CO and H2 continuously increase overall. High temperatures promote the deep cracking of biomass glycosidic bonds and LDPE carbon chains, while simultaneously driving the forward water-gas shift reaction. The volume fractions of CO2 and CH4 gradually decrease with increasing temperature. Under high-temperature conditions, methane steam reforming and CO2 reduction reactions are significantly activated, consuming both types of small carbon oxide molecules. Overall, the hydrogen concentration reaches its peak at 800℃, which is the optimal temperature for hydrogen production in this blended system. As the temperature continues to rise to 900℃, the increase in hydrogen production slows down. Excessively high temperatures trigger reverse water-gas shift side reactions, inhibiting further hydrogen generation to some extent.

[0049] Depend on Figure 6 It can be seen that the total gas production increases continuously with increasing temperature, indicating that the promotion of overall gasification conversion by high temperature is global. However, hydrogen production does not increase synchronously, decreasing from 0.286 Nm³ in the 600℃ to 800℃ range. 3 / kg increased to 0.676 Nm 3 / kg, dropping to 0.58 Nm at 900℃. 3 / kg. Hydrogen production reaches an inflection point at 800℃, and... Figure 6 The decrease in H2 volume fraction at 900℃ is consistent with this.

[0050] 3. Effect of steam ratio on gas generation characteristics of microcrystalline cellulose-LDPE blend system Gas product analysis was performed using an Agilent 7890B gas chromatograph with online detection and a TCD detector for quantitative analysis of H2, CO, CO2, and CH4. The gasification experiment was conducted in a fixed-bed reactor. As analyzed in point 5 above, the optimal gasification temperature for H2 production is 800℃. Therefore, the gasification temperature was fixed at 800℃. Microcrystalline cellulose and LDPE were blended at a mass ratio of 1:1, and the steam ratio S / B was investigated within the range of 0.5 to 2.0.

[0051] Depend on Figure 7 It can be seen that as the steam ratio increases from 0.5 to 2.0, the CO volume fraction shows a continuous decreasing trend. The H2 volume fraction reaches its maximum value at S / B=1.5, and decreases at S / B=2.0. CO2 fluctuates slightly between 6% and 8%, while CH4 shows a significant decrease from S / B=0.5 to S / B=1.0, exhibiting a V-shaped change of first decreasing and then increasing.

[0052] The continuous decrease in CO indicates that the increase in water vapor partial pressure shifts the equilibrium of the water-gas shift reaction to the right, accelerating the conversion of CO to H2. H2 reaches its peak at S / B = 1.5 and then slightly decreases, which is related to the thermodynamic characteristics of the water-gas shift reaction. This reaction is exothermic, and the driving effect of excess water vapor on the equilibrium position diminishes marginally. Simultaneously, water vapor acts as a diluent gas, reducing the partial pressure of the reactants and affecting the gas-solid contact efficiency. The change in CH4 content from initial decrease to increase indicates that appropriate amounts of water vapor promote the methane reforming reaction, leading to a decrease in CH4 content. However, when S / B exceeds 1.5, excess water vapor has a dilution effect on the reaction system, reducing the driving force of the reforming reaction and slowing down the CH4 consumption rate. Considering the performance of H2 volume fraction under various conditions, a higher hydrogen content can be obtained at S / B = 1.5.

[0053] Depend on Figure 8 It can be seen that as the steam ratio S / B gradually increases, both the total gas production and hydrogen production show a trend of first increasing and then decreasing, with both indicators reaching their peak at S / B=1.5. An appropriate amount of steam can effectively drive forward hydrogen production reactions such as water-gas shift and methane reforming, improving the degree of feedstock conversion and total gas production. When the steam ratio exceeds 1.5, excessive steam will dilute the reaction atmosphere in the reactor, lower the system reaction temperature, inhibit the forward gasification and reforming reaction, and ultimately cause a simultaneous decline in both total gas production and hydrogen production. This result is consistent with the variation law of gas volume fraction under the same variable, confirming that S / B=1.5 is the optimal steam ratio for the microcrystalline cellulose-LDPE blended system.

[0054] 4. Effect of vaporization temperature on gas production characteristics of xylan-LDPE blend system Temperature gradient experiments were conducted on xylan-LDPE co-gasification in a segmented fixed-bed gasification reactor, with four temperature conditions set at 600℃, 700℃, 800℃, and 900℃. Figure 9 It can be seen that as the gasification temperature gradually increases, the CO concentration continues to rise significantly. High temperature promotes the deep cracking of xylan glycosidic bonds and LDPE carbon chains, resulting in a continuous increase in CO production. The hydrogen concentration first increases and then slightly decreases, reaching a peak at 700℃. In the early stage of temperature rise, it effectively promotes hydrogen production through the water-gas shift reaction. After the temperature exceeds 700℃, the reverse water-gas shift reaction is activated, which inhibits hydrogen production. The concentrations of CO2 and CH4 generally decrease continuously with increasing temperature. Under high temperature conditions, the methane steam reforming and carbon dioxide reduction reactions continuously consume these two gaseous components.

[0055] Depend on Figure 10 It can be seen that the total gas production shows a continuous upward trend with the increase of gasification temperature. This change is essentially due to the regulatory effect of temperature on the depth of macromolecular cracking. In the low-temperature range, the xylan branched structure can only undergo preliminary depolymerization, the cracking reaction of LDPE long-chain alkanes is weak, and a large amount of organic matter remains in the solid residue, resulting in a low overall gasification conversion rate. As the system temperature gradually increases, the degree of xylan glycosidic bond breakage deepens, the acetyl side chain removal reaction tends to be complete, and the thermal cracking threshold of polyethylene carbon chain is broken. More solid organic matter is converted into gaseous small molecules. Combined with the promoting effect of steam gasification reforming reaction, the overall conversion efficiency of raw materials steadily improves. Therefore, the total gas production increases continuously with the increase of temperature.

[0056] The hydrogen production per unit feedstock exhibits a characteristic of first increasing and then decreasing, with the peak value corresponding to the 700℃ operating condition. During the temperature increase from 600℃ to 700℃, the temperature rise effectively activates the reversible water-gas shift reaction. Carbon monoxide generated from xylan cracking continuously reacts with water vapor to convert into hydrogen and carbon dioxide. Simultaneously, the alkane intermediates generated from LDPE cracking undergo steam reforming, further consuming water vapor in the system to generate hydrogen. The synergistic effect of multiple forward hydrogen production pathways drives a rapid increase in hydrogen production. However, as the temperature exceeds 700℃ and continues to rise, the competitive advantage of the reverse water-gas shift reaction gradually strengthens. This side reaction consumes existing hydrogen and carbon dioxide to regenerate carbon monoxide and water vapor, offsetting some of the benefits from forward hydrogen production. Furthermore, excessively high temperatures can exacerbate the polymerization and coking reactions of volatile components, consuming some active precursors, ultimately causing hydrogen production to decline as the temperature further increases.

[0057] 5. Effect of steam ratio on gas production characteristics of xylan-LDPE blend system A single-factor experiment on the vapor ratio of xylan-LDPE blended co-gasification was conducted in a segmented fixed-bed gasification unit. Four gradient operating conditions were set up with S / B = 0.5, 1.0, 1.5, and 2.0. The gasification mixture was introduced into an Agilent 7890B gas chromatograph, and the volume fraction was quantitatively detected by using a TCD detector combined with the external standard method.

[0058] Depend on Figure 11It can be seen that as the steam ratio gradually increases, the CO volume fraction generally shows a continuous downward trend. This is essentially because the increased supply of steam in the system continuously drives the forward water-gas shift reaction. The CO generated from the cracking of xylan and LDPE continuously reacts with H2O to convert into H2 and CO2, consuming CO in the system and causing its proportion to gradually decrease. The hydrogen concentration generally shows a pattern of first rising, reaching a peak at S / B=1.5, and then slightly decreasing. At lower steam ratios, the reactant water content is insufficient, and the water-gas shift and alkane steam reforming reactions are limited by the feedstock ratio, preventing the hydrogen production reaction from proceeding fully. When the steam ratio is increased to 1.5, the steam can match the reaction requirements of the cracking intermediates, maximizing the driving of both types of hydrogen production reactions, resulting in the most significant hydrogen enrichment effect. However, further increasing the steam ratio to 2.0, excessive steam dilutes the concentration of gaseous components in the reactor, lowers the effective temperature of the reaction system, weakens the efficiency of molecular collision reactions, inhibits the forward hydrogen production reaction, and ultimately causes a slight decrease in the hydrogen volume fraction.

[0059] CO2 concentration steadily increases with increasing steam ratio. This is due to two factors: firstly, the continuous generation of carbon dioxide from the water-gas shift reaction; and secondly, the continuous consumption of CH4 and generation of CO2 from the methane reforming reaction under sufficient steam conditions. These two factors drive the slow increase in concentration. The overall CH4 concentration shows a slight decrease followed by a slight rebound. In the low to medium steam range, the consumption effect of the methane reforming reaction is dominant. As excess steam leads to a decrease in system reactivity, the methane consumption rate slows down, and the proportion of CH4 shows a slight rebound.

[0060] Depend on Figure 12 It can be seen that the total gas production and the hydrogen production per unit feedstock show the same trend, both initially increasing with the increase of the steam ratio, reaching a peak at S / B=1.5, and then slightly decreasing. An appropriate amount of steam can fully drive the water-gas shift and hydrocarbon reforming reactions, improving feedstock conversion rate and hydrogen production revenue; when the steam ratio is too high, excessive steam dilutes the reaction system, reduces reaction efficiency, inhibits forward gasification, and causes both indicators to decline simultaneously. This conclusion is corroborated by the variation law of gas phase components, determining S / B=1.5 as the optimal steam ratio for this system.

[0061] 6. Effect of gasification temperature on gas production characteristics of alkali lignin-LDPE blend system Temperature gradient experiments were conducted on the co-gasification of alkali lignin and LDPE in a segmented fixed-bed gasification reactor. Four temperature conditions were set: 600℃, 700℃, 800℃, and 900℃. The gas components were quantitatively determined using an Agilent 7890B gas chromatograph with a TCD detector. Alkali lignin consists of a large molecular skeleton composed of numerous phenylpropane aromatic units cross-linked through ether and carbon-carbon bonds. Its overall bond energies are relatively high, and the activation energy required for cleavage is significantly higher than that of the two polysaccharide components. Its structural characteristics directly determine the temperature-dependent changes in gas production. Figure 13It can be seen that as the temperature gradually increases, the alkyl, phenolic hydroxyl, and ether bonds of the alkali lignin side chains gradually break, and a large number of oxygen-containing intermediates undergo decarbonylation to generate CO. Therefore, the CO volume fraction continues to rise with increasing temperature. The hydrogen concentration shows a trend of first rising and then falling, reaching a peak at 800℃: when the temperature rises to the 800℃ range, the CO generated by the cracking of alkali lignin can fully participate in the water-gas shift reaction, and the LDPE cracking of alkane intermediates simultaneously undergoes steam reforming reaction. The two pathways synergistically promote hydrogen enrichment. After the temperature exceeds 800℃, the competition of the reverse water-gas shift reaction intensifies. At the same time, excessively high temperatures easily induce aromatic free radical condensation and coking, consuming active cracking precursors, and finally the hydrogen proportion falls back. The methoxy and carboxyl groups in the alkali lignin molecule easily decompose to generate CO2 at low temperatures. As the temperature rises, CO2 participates in the carbon reduction reaction and is consumed. At the same time, methane undergoes steam reforming reaction and continuously consumes CH4, ultimately causing the overall CO2 and CH4 concentrations to gradually decrease with increasing temperature.

[0062] Depend on Figure 14 It can be seen that the total gas production increases continuously with increasing temperature, indicating that the heating gradually breaks down the lignin side chain and ether bond structure, while promoting the deep cracking of the long carbon chain of LDPE. More solid organic matter is converted into gaseous small molecules, and the overall gasification conversion rate of the raw materials continues to improve. Hydrogen production shows a trend of first increasing and then decreasing, reaching a peak at 800℃. In the 800℃ range, the carbon monoxide produced by lignin cracking undergoes a full water-gas shift reaction, and the cracking of alkanes by LDPE simultaneously undergoes steam reforming. The two pathways synergistically increase hydrogen production. After the temperature exceeds 800℃, the thermodynamic advantages of the reverse water-gas shift reaction become prominent. At the same time, high temperature easily induces aromatic free radical condensation and coking, consuming cracking active intermediates, causing hydrogen production to gradually decline.

[0063] 7. Effect of steam ratio on gas production characteristics of alkali lignin-LDPE blend system A single-factor experiment on the steam ratio of alkali lignin-LDPE blended co-gasification was conducted in a segmented fixed-bed gasification reactor. Four gradient operating conditions were set up with S / B = 0.5, 1.0, 1.5, and 2.0. The gasification mixture was introduced into an Agilent 7890B gas chromatograph, and the volume fractions of CO, H2, CO2, and CH4 were quantitatively detected using a TCD detector combined with the external standard method. The error bars in the figure reflect the data dispersion of the three parallel experiments, demonstrating the repeatability of the experiment.

[0064] Alkali lignin is an aromatic macromolecule formed by the cross-linking of phenylpropane units with carbon-carbon bonds via ether bonds. Its overall chemical bond cleavage activation energy is relatively high, and its structural characteristics dominate the evolution of gas-producing components with the vapor ratio. Figure 15It can be seen that as the steam ratio gradually increases, the CO volume fraction generally shows a characteristic of first decreasing and then slightly increasing. Under low water vapor conditions, the lignin side chains and ether bonds break down upon heating to generate a large amount of carbon monoxide. After the amount of water vapor added increases, the water vapor shift reaction continues to consume carbon monoxide, causing its proportion to drop. After the reaction system is diluted by excessive steam, the CO consumption efficiency weakens and the concentration rebounds slightly. The H2 concentration initially rises, peaks at S / B=1.5, and then slightly declines. At lower steam ratios, insufficient water supply hinders the full progress of water-gas shift and alkane steam reforming reactions due to reactant concentration limitations. This also limits the hydrogen production potential of lignin and LDPE cracking intermediates. When the steam ratio is increased to 1.5, the water and steam can match the reaction requirements of the two types of feedstock cracking intermediates, maximizing the simultaneous forward driving of the two hydrogen production reaction pathways and resulting in the most significant hydrogen enrichment effect. Further increasing the steam usage to 2.0 leads to excessive water vapor diluting the concentration of gaseous components in the reactor, reducing the effective reaction temperature, weakening molecular collision reaction efficiency, and inhibiting the forward hydrogen production reaction, ultimately causing a slight decrease in the hydrogen volume ratio. CO2 concentration initially rises steadily with increasing steam ratio, then falls slightly. This is due to two factors: firstly, the continuous generation of carbon dioxide from the water-gas shift reaction; and secondly, the continuous consumption of CH4 and generation of CO2 from the methane reforming reaction under sufficient steam conditions. These two factors drive up the concentration. With excess steam, the overall gasification conversion efficiency decreases, and the increase in carbon dioxide generation slows down. The overall CH4 concentration shows a characteristic of initially decreasing slightly and then slightly rebounding. In the low-to-medium steam range, the consumption effect of the methane reforming reaction is dominant, continuously consuming the methane produced by lignin alkyl cracking. As excess steam leads to a decrease in system reactivity, the methane consumption rate slows down, and the proportion of CH4 shows a slight rebound.

[0065] Based on the evolution of gas phase components, S / B=1.5 is the optimal steam ratio for the alkali lignin-LDPE co-gasification system. This ratio can balance the positive driving effect of water-gas shift and reforming reaction, and maximize the hydrogen concentration in the produced gas. This analysis and the corresponding gas production change curve form a mechanism that mutually confirms the mechanism, clarifying the intrinsic reaction logic of the steam addition amount regulating the distribution of aromatic raw material co-gasification products, and completing the optimization of key process parameters for this system.

[0066] Depend on Figure 16It can be seen that the total gas production and the hydrogen production per unit feedstock exhibit a consistent pattern of first increasing and then decreasing, with both indicators reaching their maximum values ​​at a steam ratio S / B = 1.5. The aromatic skeleton of alkali lignin has a high threshold for bond breaking. At low steam ratios, insufficient water supply limits water-gas conversion and hydrocarbon reforming reactions, making it difficult to fully convert lignin cracking intermediates. Overall, the gasification degree of the feedstock is low, resulting in weak gas and hydrogen production. As the steam ratio increases to 1.5, water and steam can effectively match lignin ether bonds, side-chain cracking products, and LDPE alkane intermediates, simultaneously promoting both types of hydrogen production reactions. The degree of organic matter gasification conversion reaches its optimal level, maximizing gas and hydrogen production benefits. Further increasing the steam ratio leads to excessive water dilution of the reaction atmosphere, lowers the effective reaction temperature, weakens the effective molecular collision efficiency, inhibits the forward gasification and reforming reactions, and causes a decline in feedstock conversion efficiency, resulting in a decrease in total gas and hydrogen production. The changing pattern corroborates the evolution logic of the corresponding gas phase components, clearly indicating that S / B=1.5 is the optimal steam ratio for this system, directly demonstrating the regulatory effect of steam usage on the co-gasification conversion efficiency and hydrogen production potential of aromatic biomass.

[0067] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for staged gasification catalytic hydrogen production from biomass and waste plastics, characterized in that: Inert gas is introduced into the two-stage tubular furnace to create an inert reaction atmosphere. After heating the two-stage tubular furnace, steam is introduced. Then, biomass and waste plastic are mixed and loaded into the gasification reaction zone of the two-stage tubular furnace. The catalyst is loaded into the catalytic reforming reaction zone of the same reactor. The gasification reaction is carried out at high temperature. After the reaction is completed, the gas flows with the inert gas to the catalytic reforming zone for catalytic reaction. After the catalytic reaction is completed, the gas is successively condensed and dried for recovery.

2. The method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1, characterized in that: The biomass is any one of microcrystalline cellulose, xylan, and alkali lignin.

3. The method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1, characterized in that: The catalyst is Fe / CaO-Al2O3, and the ratio of the catalyst to the total mass of biomass and waste plastics is 1:

1.

4. The method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1, characterized in that: The temperature of the gasification reaction is 600-900℃, and the temperature of the catalytic reaction is 800℃.

5. The method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1, characterized in that: The ratio of water vapor to the total mass of biomass and waste plastics is 0.5-2.

0.

6. A method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1 or 2, characterized in that: The mass ratio of biomass to waste plastic is 1:

1.

7. The method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1, characterized in that: The waste plastic is low-density polyethylene.

8. The method for staged gasification catalytic hydrogen production from biomass and waste plastics according to claim 1, characterized in that: Biomass and waste plastics were dried at 105°C for 10 hours, then crushed and passed through an 80-mesh sieve.